Padrões de herbivoria de espécies lenhosas de cerrado ralo em Uberlândia - MG. - Becker, Ingrid Savastano (2017)
Herbivory directly impacts the fitness of attacked plants, and can modify the population and plant community. To avoid herbivory, plants present strategies that could be either chemical, physical or phenological. Defense mechanisms tend not to be totally active in young leaves, which are the primary target of herbivores due to their high concentrations of water and nutrients, and their low hardness. In Cerrado, plants present few chemical defenses, making use of the reduced nutritional quality and the tolerance to damage as their main defense strategies. Despite of being well-known, it is still unclear if these plants avoid herbivory by phenological mechanisms. Here we tested four hypotheses: (i) If leaf consumption rate varies between Cerrado plant species. (ii) If the variation of leaf hardness affects the damage rate. (iii) If the budding pattern influences the damage rates. (iv) If species with different deciduousness patterns present different damage rates. The study was performed in a “cerrado ralo” area, between July 2015 and June 2016, with 14 Cerrado woody plant species. To characterize the budding patterns, we used the Índice de Atividade (IA) and the Percentual de Intensidade de Fournier (PIF). We marked up to 10 young leaves without any apparent damage for the calculation of herbivory rates. All species presented synchronic leaf production events, with peaks in October and November. The budding peak occurred in October for all species, except for S. ferrugineus, which had its peak in November. For evergreen species, the leaf production intensity was moderate while semi-deciduous and deciduous plants presented high budding intensity. We found a strong positive correlation between the percentage of budding individuals and budding intensity. Most leaves and individuals presented low herbivory damage, with significant variation between studied species. The community herbivory rate was 7.65% (±19.19 SD). We could not detect a correlation between species damage rate and specific leaf area. No difference in herbivory rates according to the species deciduousness patterns was found. Damage rate did not vary between species following the budding synchrony either. We observed a tendency of damage rates to increase as plants budding intensified. Our results show that, in a general way, plants consumption by cerrado herbivores may be low, and that it strongly varies between species or even individuals of each species. We also report an increasing tendency of damage as plants budding events became more numerous between August and November. This result suggests that plants do not temporally escape from herbivores in the studied area.